Teratoma ovariano maduro gigante em gestante de primeiro trimestre - Nayane Peixoto Soares; Gabriela Mesquita Pontes; Fernanda Mendonça Salles Ghannam; Henri Naves e Siqueira; Daniel Fernandes Correia Júnior; Waldemar Naves do Amaral (Revista Goiana de Medicina, 2026)
Introduction: Mature cystic teratoma is the most frequent ovarian neoplasm in reproductive-aged women, posing maternal and fetal risks when diagnosed during pregnancy. Objectives: To report the diagnosis and surgical management of a giant ovarian teratoma in a first-trimester pregnant patient. Methods: A descriptive case report study of a 17-year-old primigravida with a 30 cm adnexal mass concomitant with a 12-week intrauterine pregnancy. Results: Exploratory laparotomy with partial drainage of the contents was performed to enable tumor excision, and histopathology confirmed a mature cystic teratoma associated with a mucinous cystadenoma. Prenatal follow-up revealed a borderline lateral ventricle and progression to intrauterine growth restriction (IUGR) in the third trimester, leading to labor induction at 38 weeks. Conclusions: This case reinforces the necessity of timely surgical intervention for voluminous adnexal masses during pregnancy and the importance of rigorous obstetric surveillance to monitor perinatal outcomes potentially associated with early surgical stress.